Fat of the Gut: Epithelial Phospholipids in Inflammatory Bowel Diseases - Lidiya V. Boldyreva (MDPI AG, 2021)
Inflammatory bowel diseases (IBD) comprise a distinct set of clinical symptoms resulting from chronic inflammation within the gastrointestinal (GI) tract. Despite the significant progress in understanding the etiology and development of treatment strategies, IBD remain incurable for thousands of patients. Metabolic deregulation is indicative of IBD, including substantial shifts in lipid metabolism. Recent data showed that changes in some phospholipids are very common in IBD patients. For instance, phosphatidylcholine (PC)/phosphatidylethanolamine (PE) and lysophosphatidylcholine (LPC)/PC ratios are associated with the severity of the inflammatory process. Composition of phospholipids also changes upon IBD towards an increase in arachidonic acid and a decrease in linoleic and a-linolenic acid levels. Moreover, an increase in certain phospholipid metabolites, such as lysophosphatidylcholine, sphingosine-1-phosphate and ceramide, can result in enhanced intestinal inflammation, malignancy, apoptosis or necroptosis. Because some phospholipids are associated with pathogenesis of IBD, they may provide a basis for new strategies to treat IBD. Current attempts are aimed at controlling phospholipid and fatty acid levels through the diet or via pharmacological manipulation of lipid metabolism.